2016
DOI: 10.1017/s0031182016001967
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defense of Nrf2vspro-inflammatory system of NF-κB during the amoebic liver infection in hamster

Abstract: Entamoeba histolytica is the causative agent of amoebic liver abscess (ALA), which course with an uncontrolled inflammation and nitro-oxidative stresses, although it is well known that amoeba has an effective defence mechanisms against this toxic environment, the underlying molecular factors responsible for progression of tissue damage remain largely unknown. The purpose of the present study was to determine during the acute stage of ALA in hamsters, the involvement of nuclear factor (erythroid-derived 2)-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 59 publications
(94 reference statements)
3
9
0
Order By: Relevance
“…Our results show that amebic liver lesions are visible at 12 h, which was consistent with increased serum enzyme activity for ALT and γ-GTP; these results agreed with previous findings [ 1 ]. ALT is an enzyme located in the cytosol of hepatocytes [ 49 ], and in the present study, we observed slightly elevated levels, possibility because serum evaluation was performed at 12 h post-liver infection (ALA group).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results show that amebic liver lesions are visible at 12 h, which was consistent with increased serum enzyme activity for ALT and γ-GTP; these results agreed with previous findings [ 1 ]. ALT is an enzyme located in the cytosol of hepatocytes [ 49 ], and in the present study, we observed slightly elevated levels, possibility because serum evaluation was performed at 12 h post-liver infection (ALA group).…”
Section: Discussionsupporting
confidence: 93%
“…It is known that at 12 h of amebic liver infection, the amount of polymorphonuclear leukocytes infiltrated and the lesion size are increased, forming microabscesses [ 63 ]. In addition, in a previous study [ 1 ], we reported that at this time, the increase in oxidative stress is greatest and the NF-κB pro-inflammatory pathway is activated. Moreover, the effect of the SNS and PNS during the early and late stages of amebic infection has also begun to be studied [ 3 , 42 , 51 ], but there is little knowledge on their participation and their relationship with the oxidative stress that is generated during the first hours of amebic infection.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations